Good Practices in Human Resource Management in the Corporate Environment in Indonesia - Udayana, Agung; Prasetyo, Hari; Saragih, Herlina Juni Risma (International Journal of Science Education and Technology Management, 2024)
This research examines best practices in human resource management (HR) in large companies in Indonesia. The background is the importance of effective HR management in increasing a company's competitiveness amidst global competition. The aim of the research is to identify and analyze HR strategies that are proven to be effective. The method used is descriptive qualitative analysis with data obtained from a comprehensive literature review. This research identified several best practices, such as e-recruitment, employer branding, training evaluation using the Kirkpatrick model, career development programs, and the use of technology in measuring employee performance. The results show that these practices are significant in improving organizational performance and employee well-being. Successful implementation is supported by effective leadership, employee involvement, technology, and a supportive culture and infrastructure. In conclusion, best practices in HR management contribute to improving employee performance and welfare, as well as company competitiveness. This practice is relevant both locally and globally, so it needs to be adopted and adapted by companies to increase efficiency and competitiveness.